Suturing under tension in minimally invasive surgery: a comparison of three intracorporeal knot types - Romero, Philipp; Kessler, Hans; Fuchs, Juri; Willuth, Estelle; Pianka, Frank; Günther, Patrick (Langenbeck's archives of surgery, 2025)
Intracorporeal knot tying (ICKT) and suturing under tension are essential skills for performing advanced minimally invasive surgery (MIS) procedures. Over recent years, various intracorporeal knot types with specific properties have been developed. The classical surgical square knot (CSK) continues to be used as the standard knot in MIS. Previously published studies suggested that the security of the surgical square knot improves when the knot throw combination is adjusted from four wraps (2W1W1W) to five wraps (3W1W1W). Additionally, the intracorporeal slipping knot (SLK) has been found to be superior to the CSK in sutures under tension. This study aimed to compare ICKT of the CSK, a modified square knot (MSK) and the SLK during simulated suture placement under tension.